Analysis of WLAN Network Quality Improvement at Bank Mandiri Palembang Sudirman Area using Per Connection Queue Method - Misinem, .; Tri Basuki, Kurniawan; Nurul Adha, Oktarini S.; Siti Nurdiana, . (INTI International University, 2023)
With the internet's and information technology's rapid expansion, IT has emerged as a crucial component of many areas, particularly computer networks. Network monitoring is crucial because it can assist in locating network issues precisely, and ongoing monitoring can help spot any problems early on and take proactive measures to fix them before they negatively affect users. The purpose of this study is to track and evaluate the functionality of the Palembang Sudirman area's Bank Mandiri WLAN (Wireless Local Area Network). Three steps make up the action research approach used in this study: diagnosis, analysis, and assessment. This allows adjustments to be made to the scenario-specific protocols that could otherwise result in alterations. Based on Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON) standards and Quality of Service (QoS), the analysis concludes that Bank Mandiri's WLAN is rated as exceptional. The delay value decreased from 32 ms to 8 ms and the number of packet losses decreased from 1.5% to 0 when the PCQ method was implemented.